muNet: Harnessing Multiuser Capacity in Wireless Mesh Networks - Li, Li Erran; Alimi, Richard; Ramjee, Ramachandran; Viswanathan, Harish; Yang, Yang Richard (Proceedings of IEEE Infocom Mini Symposium, 2009)
We present muNet, a wireless mesh network design and implementation to harness the multiuser capacity of wireless channels. Traditionally, media access control is designed to schedule one transmission between one sender and one receiver without interference at any given time. However, this design is suboptimal in terms of achieving the multiuser capacity of multi-access wireless channels. In muNet, we implement effective physical layer techniques called superposition coding and successive interference cancellation to enable simultaneous unicast transmissions from a single transmitter to multiple receivers as well as from multiple transmitters to a single receiver. We design the first practical MAC protocol that leverages such a physical layer and exposes the multiuser capacity to upper layers. We also present a simple, effective routing protocol that increases simultaneous transmission opportunities for the MAC layer. A proof-of-concept muNet is implemented on the GNU Radio platform. Measurements on the implementation shows that the throughput gains of muNet are significant (up to 93%).
We present muNet, a wireless mesh network design and implementation to harness the multiuser capacity of wireless channels. Traditionally, media access control is designed to schedule one transmission between one sender and one receiver without interference at any given time. However, this design is suboptimal in terms of achieving the multiuser capacity of multi-access wireless channels. In muNet, we implement effective physical layer techniques called superposition coding and successive interference cancellation to enable simultaneous unicast transmissions from a single transmitter to multiple receivers as well as from multiple transmitters to a single receiver. We design the first practical MAC protocol that leverages such a physical layer and exposes the multiuser capacity to upper layers. We also present a simple, effective routing protocol that increases simultaneous transmission opportunities for the MAC layer. A proof-of-concept muNet is implemented on the GNU Radio platform. Measurements on the implementation shows that the throughput gains of muNet are significant (up to 93%).